A study of the surface viscoelasticity of poly(vinyl acetate) at the air-water interface using the electrocapillary wave diffraction technique - Skarlupka, R; Seo, Y; Yu, HU (ELSEVIER SCI LTD, 1998)
The surface viscoelastic properties of poly(vinyl acetate) (PVAc), spread as a monolayer at the air-water interface, were determined using the electrocapillary wave diffraction (ECWD) technique with the Wilhelmy plate method for static surface tension measurements. Surface longitudinal viscosity, kappa, and elasticity, epsilon, were calculated from the dispersion equation for surface waves over a range of surface concentrations. The static and dynamic elasticities were in agreement at the low surface concentrations but showed some differences at higher concentrations. The difference in surface viscoelastic properties measured by ECWD and by surface quasi-elastic light scattering (SLS) was ascribed to the difference in monolayer response to waves of different wavelengths. Because of the relatively long wavelengths of ECWD capillary waves, the monolayer surface elasticities measured by ECWD were smaller than the static elasticities in the concentration range where maximum damping due to the resonance between the longitudinal wave and the transverse capillary wave occurs. (C) 1997 Elsevier Science Ltd.
Keywords: LIGHT-SCATTERING; POLYVINYL ACETATE); POLY(ETHYLENE OXIDE); CAPILLARY WAVES; MONOLAYERS; FILMS; POLY(DIMETHYLSILOXANE); PROPAGATION; DEPENDENCE; LAYERS